1998
DOI: 10.1016/s1074-7613(00)80477-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-13, IL-4Rα, and Stat6 Are Required for the Expulsion of the Gastrointestinal Nematode Parasite Nippostrongylus brasiliensis

Abstract: Although IL-4 induces expulsion of the gastrointestinal nematode parasite, Nippostrongylus brasiliensis, from immunodeficient mice, this parasite is expelled normally by IL-4-deficient mice. This apparent paradox is explained by observations that IL-4 receptor alpha chain (IL-4Ralpha)-deficient mice and Stat6-deficient mice fail to expel N. brasiliensis, and a specific antagonist for IL-13, another activator of Stat6 through IL-4Ralpha, prevents worm expulsion. Thus, N. brasiliensis expulsion requires signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
503
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(526 citation statements)
references
References 53 publications
20
503
1
2
Order By: Relevance
“…These different findings may be attributable, at least in part, to the different mouse strains used in these studies. STAT-6 is required for both IL-4 and IL-13 signaling, and is essential for the expulsion of both T. spiralis and N. brasiliensis from the intestine (20,21). We have shown that IL-13 (and IL-4R␣), but not IL-4, is required for T. spiralis expulsion.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These different findings may be attributable, at least in part, to the different mouse strains used in these studies. STAT-6 is required for both IL-4 and IL-13 signaling, and is essential for the expulsion of both T. spiralis and N. brasiliensis from the intestine (20,21). We have shown that IL-13 (and IL-4R␣), but not IL-4, is required for T. spiralis expulsion.…”
Section: Discussionmentioning
confidence: 78%
“…However, expulsion is inhibited in mice deficient in the IL-4/IL-13 signaling molecules IL-4R␣ or STAT6, suggesting a role for IL-13 (19,20). IL-13 is certainly critical for expulsion of another gastrointestinal nematode, Nippostrongylus brasiliensis, which inhabits the lumen of the small intestine (21), and resolution of Trichuris muris infection of the large bowel is also dependent on IL-13 via the production of TNF-␣ (22). In addition, both T. muris (23) and N. brasiliensis (24) infection generate changes in mucosal tissue architecture, including villus atrophy, crypt hyperplasia, and thickening of the muscularis externa.…”
mentioning
confidence: 99%
“…Nevertheless, IL-13 is by all accounts the most pivotal, being required for protection against most parasitic nematodes, [60][61][62][63] perhaps for its role in supporting the migration of dendritic cells that subsequently drive adaptive immunity. 64,65 IL-13 is also critical for inducing many of the expulsion mechanisms in the intestine that will be discussed further on.…”
Section: Transmissionmentioning
confidence: 99%
“…66 Furthermore, with the exception of IL-4 in the skin, 67 IL-4 appears to be dispensable for N. brasiliensis expulsion. 61,68 The redundancy between IL-4 and IL-13 likely stems from their shared usage of the IL-4Ra subunit, [69][70][71] although interestingly, IL-4Ra deficiency in T cells has no impact on worm expulsion during either T. spiralis, 72 H. polygyrus, 73 or N. brasiliensis 61,62 infections, in contrast to total IL-4Ra ablation. 63,[73][74][75] Instead, IL-4 might need to be produced rather than recognized by T cells, as it is mostly secreted by follicular helper T cells to promote IgG1 class switching of B cells.…”
Section: Transmissionmentioning
confidence: 99%
“…Like IL-4, IL-13 up-regulates CD23, CD71 and MHC class II expression on B cells and monocytes [32], elicits B cell proliferation and induces IgG4 and IgE production by human B cells [32], and promotes Th2 cell differentiation [33]. In addition, IL-13 plays a dominant role to IL-4 in mediating worm expulsion to Nippostrongylus brasiliensis [34], exerts protective functions both in the chronic stages of some Leishmaniasis major infections [35] and in Listeria monocytogenes infection in the context of a Th1 cytokine response [36], and acts as the key mediator in the pathogenesis of allergic asthma [37]. Studies of T. muris showing that IL-13 mediates host protection in IL-4 -/-BALB/c mice suggest an IL-4-independent role for IL-13 in resistance to T. muris [38].…”
mentioning
confidence: 99%